2022
DOI: 10.7759/cureus.22090
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Cocaine Use and Manifestations in Hospitalized Patients: A Cross-Sectional Study

Abstract: Objective About 41 million people aged ≥18 years reported lifetime use of cocaine, and 5.4 million people reported having used cocaine in 2019. We aim to identify trends of cocaine use, manifestations, concomitant drug use, and financial burden on health care among hospitalized patients. Methods We utilized National Inpatient Sample from years 2006-2018. Patients with age ≥18 years, admitted to the hospital with a diagnosis of cocaine abuse, dependence, poisoning, or unspecifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…An in-hospital mortality study performed in a national inpatient sample in the U.S. ( n = 261,000,000; between 2006 and 2018) compared cocaine to cocaine–alcohol positive patients, admitted with a diagnosis of cocaine abuse, dependence, poisoning, or unspecified cocaine use. The results showed a higher rate of in-hospital mortality for cocaine–alcohol compared with cocaine alone (1.36% and 1.07%, respectively; p < 0.001), but this difference was no longer statistically significant ( p = 0.87) after adjustment for a number of covariates, like age, sex, race, and comorbid conditions [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-hospital mortality study performed in a national inpatient sample in the U.S. ( n = 261,000,000; between 2006 and 2018) compared cocaine to cocaine–alcohol positive patients, admitted with a diagnosis of cocaine abuse, dependence, poisoning, or unspecified cocaine use. The results showed a higher rate of in-hospital mortality for cocaine–alcohol compared with cocaine alone (1.36% and 1.07%, respectively; p < 0.001), but this difference was no longer statistically significant ( p = 0.87) after adjustment for a number of covariates, like age, sex, race, and comorbid conditions [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a potent sympathomimetic drug, cocaine is associated with considerable cardiovascular complications [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], including angina pectoris, coronary vasospasm, myocardial ischemia, acute myocardial infarction (AMI), cerebrovascular disease, ventricular arrhythmias, and sudden cardiac death. Therefore, it is no surprise that cocaine is one of the main causes of drug-related emergency department (ED) visits, due to cardiovascular problems [ 11 ], with chest pain mentioned as the most common complaint [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Between 2000 and 2017, older adults showed greater increases in proportions admitted for cocaine/crack relative to younger adults [ 49 ]. Gangu et al found that there has been an uptrend in hospital admissions in the U.S. with a primary diagnosis of cocaine abuse, dependence, poisoning, or unspecified cocaine use from 2016 to 2018, with patients over 50 years old comprising only 21.2% of admissions in 2006 compared to 43.27% in 2018 [ 50 ]. Further research must be done to better understand trends in order to address appropriate screening, diagnosis, and treatment of older patients.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the existing literature, this study presents cocaine use trends specific to reproductive age females, with or without other drug use. It is worth noting that other studies examining trends of cocaine use in the US general population have warned of a similar noticeable uptake in use of this drug 18 . As highlighted in a recent study that included responses from all subgroups of US adults, a similar initial decrease in past 12‐month cocaine use prevalence was observed from 2006 to 2011 (2.5% in 2006–2007 to 1.7% in 2010–2011), before an uptake in use was documented in 2018–2019 (2.1%) 5 .…”
Section: Discussionmentioning
confidence: 95%